The receptor for advanced glycation end products RAGE is involved in corneal healing - Naß, Norbert; Kaiser, Delia; Sel, Saadettin (Annals of anatomy, 2017)
Impaired corneal healing is still a major cause of blindness. As RAGE (receptor for advanced glycation endproducts) is involved in inflammation and wound healing in other tissues, we here investigated its relevance for corneal wound healing. Corneal re-epithelialization after alkaline injury was analysed in an ex-vivo approach with cultured, enucleated eyes from mice either of the C57Bl/6 NChR genotype (RAGE+/+) and mice of the same strain lacking the RAGE gene (RAGE−/−). The wound area was determined time dependently by fluorescence imaging using fluorescein staining. The eyes of RAGE−/− mice showed a significantly slower re-epithelialization than eyes of the RAGE+/− and the RAGE+/+ genotype. In immunohistochemistry, RAGE expression was increased in wounded corneas whereas the abundance of the RAGE ligand HMGB1 was unaffected, but an increase in S100b-like proteins was revealed upon injury. However, neither the addition of the RAGE agonist HMGB1 or an HMGB1 antagonising antibody nor bovine S100b protein to the culture medium of the wounded eyes had an effect on corneal wound closure in ex-vivo. Further gene expression analysis by RT-PCR demonstrated an increase in RAGE expression on the mRNA level, no significant regulation of HMGB1 and a differential regulation of the S100 gene family after alkaline burn of the cornea. In conclusion, RAGE is clearly involved in corneal re-epithelialization most probably mediated by signalling via S100 proteins.